Temporal Trends in Pulmonary Embolism Mortality Associated with COVID-19 in the United States: A 5-Year Retrospective Analysis - Lippi, Giuseppe; Mattiuzzi, Camilla (International Journal of Angiology, 2025)
Coronavirus disease 2019 (COVID-19) has been strongly associated with thrombotic complications, particularly pulmonary embolism (PE). This study aims to analyze the real-world impact of COVID-19 on PE-related mortality in the United States over the first 5 years of the pandemic. We conducted a retrospective observational study using the CDC WONDER database, combining data on mortality from PE and COVID-19 using the 10th revision of the International Classification of Diseases (ICD-10) codes I26 (PE) and U07.1 (COVID-19). The analysis spanned from 2020 to 2024. We found a peak in COVID-19-associated PE deaths in 2021, with an estimated crude rate of 211 × 1,000 PE deaths. This rate progressively declined over the following years, being 141 × 1,000 in 2022, 44 × 1,000 in 2023, and 29 × 1,000 in 2024, respectively. The estimated crude rate for COVID-19-associated PE in the United States was 111 × 1,000 PE deaths throughout the 5-year period. The results of our study show that COVID-19 may have contributed to nearly one-tenth of all PE deaths throughout the first 5 years of the pandemic. Despite the gradual decline over the years since its peak in 2021, the still sustained mortality suggests ongoing thrombotic risks, especially impacting high-risk populations, emphasizing the need for continued vigilance and prevention of thrombotic complications in COVID-19 patients.
Keywords: mortality; COVID-19; pulmonary embolism